The art of teaching online : how to start and how to succeed as an online instructor - Cooperman, Larry (Chandos Publishing, 2018)
The Art of Teaching Online: How to Start and How to Succeed as an Online Instructor focuses on professionals who are not teachers, but who wish to enter the online education field as instructors in their disciplines. This book focuses mainly on how potential online instructors can create and maintain the human aspect of live, face-to-face education in an online course to successfully teach and instruct their students. Included are interviews with experienced online instructors who use their emotional intelligence skills and instruction skills (examples included) to teach their students successfully. Includes interviews with experienced instructors.